Disyllabic post-nominal locatives in Mandarin Chinese - Kuo, Pei-Jung (Linguistik Online, 2021)
In this paper, I focus on disyllabic post-nominal locatives in Mandarin Chinese. In the literature, disyllabic post-nominal locatives have traditionally been considered nouns. Recent proposals, however, have offered different analyses. In Wu (2015), the typical disyllabic post-nominal locative falls somewhere between an adposition and a noun. Djamouri/Paul/Whitman (2013) and Paul (2015) discuss some new disyllabic post-nominal locatives and propose that they are postpositions. In contrast to these analyses, I argue that the commonly analyzed disyllabic post-nominal locatives are indeed nouns, and that so too is one subtype of the locatives recently proposed to be postpositions. I further examine this subtype and discuss its unique behavior. Finally, a diachronic study of disyllabic post-nominal locatives indicates that they may not share the same analysis as mono-syllabic post-nominal locatives.